Trapping light in air with membrane metasurfaces for vibrational strong coupling - Wihan Adi; Samir Rosas; Aidana Beisenova; Shovasis Kumar Biswas; Hongyan Mei; David A. Czaplewski; Filiz Yesilkoy (Nature Communications)
Abstract Optical metasurfaces can manipulate electromagnetic waves in unprecedented ways at ultra-thin engineered interfaces. Specifically, in the mid-infrared (mid-IR) region, metasurfaces have enabled numerous biochemical sensing, spectroscopy, and vibrational strong coupling (VSC) applications via enhanced light-matter interactions in resonant cavities. However, mid-IR metasurfaces are usually fabricated on solid supporting substrates, which degrade resonance quality factors (Q) and hinder efficient sample access to the near-field electromagnetic hotspots. Besides, typical IR-transparent substrate materials with low refractive indices, such as CaF2, NaCl, KBr, and ZnSe, are usually either water-soluble, expensive, or not compatible with low-cost mass manufacturing processes. Here, we present novel free-standing Si-membrane mid-IR metasurfaces with strong light-trapping capabilities in accessible air voids. We employ the Brillouin zone folding technique to excite tunable, high-Q quasi-bound states in the continuum (qBIC) resonances with our highest measured Q-factor of 722. Leveraging the strong field localizations in accessible air cavities, we demonstrate VSC with multiple quantities of PMMA molecules and the qBIC modes at various detuning frequencies. Our new approach of fabricating mid-IR metasurfaces into semiconductor membranes enables scalable manufacturing of mid-IR photonic devices and provides exciting opportunities for quantum-coherent light-matter interactions, biochemical sensing, and polaritonic chemistry.